การพัฒนากลยุทธ์การบริหารงานวิจัยของมหาวิทยาลัยราชภัฏในกลุ่มภาคเหนือตอนล่าง - พงศ์ภิญโญโอภาส, สุภาพร; เชาวกีรติพงศ์, ทวนทอง; อรัญวงศ์, เรขา (Journal of Education and Innovation, 2013)
บทคัดย่อ การวิจัยเรื่องนี้ มีวัตถุประสงค์เพื่อ ศึกษาสภาพและปัญหาการบริหารงานวิจัย ปัจจัยที่ส่งผลต่อการบริหารงานวิจัย กลยุทธ์ และแนวทางการพัฒนาการบริหารงานวิจัยของมหาวิทยาลัยราชภัฏในกลุ่มภาคเหนือตอนล่าง ศึกษากลยุทธ์และแนวทางการพัฒนาการบริหารงานวิจัยของมหาวิทยาลัยราชภัฏที่ประสบความสำเร็จ พัฒนาและประเมินกลยุทธ์การบริหารงานวิจัยของมหาวิทยาลัยราชภัฏในกลุ่มภาคเหนือตอนล่าง โดยดำเนินการวิจัย 5 ขั้นตอน ใช้แบบสอบถาม แบบบันทึกผลการวิเคราะห์เอกสาร และแบบสัมภาษณ์แบบมีโครงสร้างเป็นเครื่องมือเก็บรวบรวมข้อมูลจัดการประชุมเชิงปฏิบัติการและการสัมมนาอิงผู้เชี่ยวชาญ เก็บรวบรวมข้อมูลจาก ผู้บริหาร อาจารย์ นักวิจัยผู้ทรงคุณวุฒิด้านการบริหารและการวิจัย แผนกลยุทธ์และรายงานประจำปีของมหาวิทยาลัยและของสถาบันวิจัยและพัฒนามหาวิทยาลัยราชภัฏในกลุ่มภาคเหนือตอนล่างและมหาวิทยาลัยราชภัฏที่ประสบความสำเร็จด้านการบริหารงานวิจัย วิเคราะห์ข้อมูลโดยคำนวณร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน วิเคราะห์การถดถอยพหุคูณแบบหลายขั้นตอน และวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1. สภาพและปัญหาการบริหารงานวิจัย รวมทั้งปัจจัยที่ส่งผลต่อการบริหารงานวิจัยของมหาวิทยาลัยราชภัฏภาคเหนือตอนล่าง โดยภาพรวมและรายด้านอยู่ในระดับปานกลาง และปัจจัยที่ส่งผลต่อการบริหารงานวิจัย ได้แก่ด้านวัฒนธรรม และด้านกฎหมาย 2. กลยุทธ์การบริหารงานวิจัยของมหาวิทยาลัยราชภัฏภาคเหนือตอนล่าง ประกอบด้วย ด้านการนำ 38กลยุทธ์ และด้านการควบคุม 3 กลยุทธ์ แนวทางการพัฒนาการบริหารงานวิจัย ประกอบด้วย ด้านการวางแผน 16ข้อ ด้านการจัดองค์การ 16 ข้อ ด้านการนำ 44 ข้อ และด้านการควบคุม 5 ข้อ 3. กลยุทธ์การบริหารงานวิจัยของมหาวิทยาลัยราชภัฏที่ประสบความสำเร็จ ประกอบด้วย ด้านการนำ 58กลยุทธ์ และด้านการควบคุม 6 กลยุทธ์ แนวทางการพัฒนาการบริหารงานวิจัย ประกอบด้วย ด้านการวางแผน 3 ข้อด้านการจัดองค์การ 11 ข้อ ด้านการนำ 75 ข้อ และด้านการควบคุม 12 ข้อ 4. กลยุทธ์การบริหารงานวิจัยที่พัฒนาขึ้น ประกอบด้วย วิสัยทัศน์ พันธกิจ เป้าประสงค์ ประเด็นกลยุทธ์กลยุทธ์ มาตรการ และตัวชี้วัด โดยมีกลยุทธ์ 9 กลยุทธ์ 5. กลยุทธ์การบริหารงานวิจัยที่พัฒนาขึ้น มีความสอดคล้อง ความเหมาะสม ความเป็นไปได้ และความเป็นประโยชน์ Abstract The purposes of this research were to study the state and the problems of the researchadministration and the factors affecting the research administration, to study the strategies andguidelines to develop research administration of Rajabhat universities in the lower northern region, tostudy the strategies and guidelines to develop research administration of the Rajabhat universitieswith best practices in research administration, to develop the research administrative strategies, and toassess the developed research administrative strategies of Rajabhat universities in the lower northernregion. The research procedures were divided into 5 steps. Data was collected by using thequestionnaire, record forms of the document analysis results, and the structured interview questions.Workshop and connoisseurship were also held by the researcher to collect the data. Data wascollected from administrators, lecturers, researchers, experts in administration and research as well asthe data collected from the strategy plans and the annual reports of Rajabhat universities andResearch and Development institutes in the lower northern region and the Rajabhat universities withbest practices in research administration. Data was analyzed using percentage, mean, standarddeviation, stepwise multiple regression analysis, and contents analysis.The findings were as follows: 1. The state and problems of research administration as well as the factors affecting researchadministration of Rajabhat universities in the lower northern region, as a whole and each aspect wereat an average level. The factors affecting the state of research administration were culture and law. 2. The research administrative strategies of Rajabhat universities in the lower northern regionwere as follows, 38 strategies for leading, and 3 strategies for controlling. The guidelines for theresearch administrative were as follows, 16 guidelines for planning, 16 guidelines for organizing, 44guidelines for leading, and 5 guidelines for controlling. 3. The research administrative strategies of the Rajabhat universities with best practices inresearch administration were as follows, 58 strategies for leading, and 6 strategies for controlling. Theguidelines for the research administrative were as follows, 3 guidelines for planning, 11 guidelines fororganizing, 75 guidelines for leading, and 12 guidelines for controlling. 4. The developed research administrative strategies consisted of vision, mission, goals,strategic issues, strategies, measures, and indicators. The research administrative strategies consistedof nine strategies. 5. The developed research administrative strategies were found be consistent, appropriate,feasible, and useful.